HAMBATAN PEMUNGUTAN PAJAK RUMAH KOS DI KOTA MADIUN - UNTUNG BAGUS PRASETYO, ANTHONIUS (Jurnal Akuntansi AKUNESA, 2018)
This research is based on the phenomenon that occurs, there are 132 (one hundred thirty two) number of illegal boarding houses in Madiun City, while there is a Regional Regulation of Madiun City Number 23 of 2011 concerning local taxes, but in reality the tax revenue of boarding houses in Madiun City is still less than optimal if seen from the potential that exists. The aim of this research was to know the obstacles of collecting the boarding house tax that executed by Revenue and Financial Management in Madiun city. The method of this research is descriptive qualitative research. The result of this research was known less than maximum in taxpayer data collection process which owns boarding house business, uneven and inefficient socialization, and lack of awareness of Madiun citizens about the importance of paying tax become one of the obstacles in implementation of boarding house tax collection in Madiun City.Keyword : tax compliance, boarding house tax, obstacles